THE ROLE OF PARENTS AND TEACHERS AS LITERACY SPONSOR FOR CHILDREN WITH DYSLEXIA DISSORDER IN TAARE ZAMEEN PAR MOVIE - Mas Alwis Imru'ul Qais As-syauqi; Pratiwi Retnaningdyah; Ali Mustofa (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
The role of parents and teachers is less to be considered in developing children’s literacy skills such reading and writing. As literacy sponsors, both parents and teachers hold a critical role for the children, especially those with special needs such dyslexic ones, in acquiring literacy skills and knowledge. This study focuses on the role of parents and teachers as literacy sponsor portrayed in Taare Zameen Par movie and how the application of multimodal literacy is depicted through the story of a dyslexic boy, Ihsaan. This study uses descriptive qualitative method to analyse and describe the data. The main data of this study are dialogues and screenshots taken from the movie. Furthermore, the data will be analysed using Brandt’s literacy and sponsorship theories to support the argumentation and interpretation in the analysis process. The result shows that the role of parents and teachers has a great impact toward the literacy development of dyslexic children like Ishaan. Likewise, multimodal literacy could give a better outcome for the children with dyslexia disorder.